Dynamic economic analysis of greenhouse pepper production on rockwool on a family farm - Tompos, D.; Bálint, J. (International Journal of Horticultural Science, 2005)
The major part of the pepper growing farms in Hungary operate as family enterprises with areas varying between 1,000 and 3,000 m2. As a result of the small size, their profitability is greatly dependant on the technological level and market circumstances. Most of these farms are characteristically affected by the lack of capital, therefore, they are unable to implement any further developments with their own forces. Greenhouse pepper production on rockwool had already been subjected to analysis earlier in our research, however, those calculations were directed solely at the profitability and efficiency of production. Based on the data from 2004 in 2005 yet another and more profound analysis was set as the objective. Besides the methods already applied before, several dynamic indicators have been introduced which could also be useful for practical applications. The graphs can permit growers to monitor the temporal distribution of the costs incurred and revenues earned during production. Thereby it is easier to plan the costs and more simple to distribute them more rationally over the production period. Our experiences suggest that this sort of analytical method is applicable only in cases where a very careful and precise collection of data is ensured and the results obtained can not be generalised as being valid only for the single farm analysed. Experiences and results, however, make us consider the dynamic economic analysis as being very useful both for beginners and practicing horticulturists.